We are not free ebook A printz honor winner. - Chee, Traci (2020)
* NATIONAL BOOK AWARD FINALIST * PRINTZ HONOR BOOK * WALTER HONOR BOOK * ASIAN/PACIFIC AMERICAN AWARD FOR LITERATURE HONOR BOOK * From New York Times best-selling and acclaimed author Traci Chee comes We Are Not Free, the collective account of a tight-knit group of young Nisei, second-generation Japanese American citizens, whose lives are irrevocably changed by the mass U.S. incarcerations of World War II. Fourteen teens who have grown up together in Japantown, San Francisco. Fourteen teens who form a community and a family, as interconnected as they are conflicted. Fourteen teens whose lives are turned upside down when over 100,000 people of Japanese ancestry are removed from their homes and forced into desolate incarceration camps. In a world that seems determined to hate them, these young Nisei must rally together as racism and injustice threaten to pull them apart.